Evaluating the search and matching model with sticky wages - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2010)
Several authors have proposed staggered wage bargaining as a way to introduce sticky wages into search and matching models while preserving individual rationality. I evaluate the quantitative implications of such an approach. I feed through a series of estimated shocks from US data into a search and matching model with sticky prices and wages. I compare the implications of how the sticky wages enter into the hiring decision, and there seems to be a tradeoff between generating business cycle volatility and matching the lack of a long-run relationship between vacancy creation and inflation. With regard to wages, the sticky wage model unconditionally does a better job at matching wages than the flexible wage model.
Keywords: E24; E25; E32; J23; J31; J63; 330; Sticky wages; sticky prices; staggered Nash bargaining; inflation; new hires; search and matching; business cycles; Konjunkturtheorie; Arbeitsmarkttheorie; Arbeitsuche; Matching; Lohnrigidität; Lohnverhandlungstheorie; Nash-Gleichgewicht; Phillips-Kurve; Theorie